Victorian Conversion Narratives and Reading Communities. By Emily Walker Heady - Gilley, Sheridan (The journal of theological studies, 2014)
Professor Heady’s work is an interpretation of four leading Victorian novels and of Oscar Wilde’s De Profundis as expressions of the tension between the worlds of the private and the public, between the inner subjective realm of experience and the outer objective region of story and language, in narratives of conversion or ‘heart change’, a genre which was classically Christian. The Victorian variation upon this is sometimes about conversion from Christianity, but it has a rich background of traditional spiritual reference, so that even when soberly realist, it is still invested with religious content in the narrative which describes it, a narrative which is itself a form of evangelism.